Reinforced ardealite aggregate, ultra-high performance concrete material and preparation method of ultra-high performance concrete material

By chemically reacting phosphogypsum with primary aluminum ash and other materials in a strong alkali solution, strengthened phosphogypsum aggregate is prepared, which is used to prepare ultra-high performance concrete with compressive strength higher than 150MPa, which solves the shortcomings of traditional concrete in high strength and durability, and effectively utilizes solid waste resources to achieve efficient, economical and environmentally friendly concrete material preparation.

CN119898978AActive Publication Date: 2025-04-29SHENYANG JIANZHU UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411891242.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-29
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Traditional concrete has shortcomings in high strength and durability, especially in large-span bridges, high-rise buildings and marine engineering structures, while solid waste resources such as phosphogypsum and primary aluminum ash have not been effectively utilized.

Method used

By mixing phosphogypsum, cement, primary aluminum ash, water and ettringite crystal form control agent, after extrusion molding, autoclaving and impregnation treatment, carbon dioxide is introduced into the strong alkali solution, and a series of chemical reactions are carried out to finally prepare strengthened phosphogypsum aggregate for the preparation of ultra-high performance concrete with a compressive strength higher than 150MPa.

Benefits of technology

Ultra-high performance concrete with high compressive strength and high durability has been achieved, solving the shortcomings of traditional concrete in terms of high strength and durability, and at the same time, it effectively utilizes solid waste resources such as phosphogypsum and primary aluminum ash, which has important economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a reinforced ardealite aggregate, an ultra-high performance concrete material and a preparation method thereof, and belongs to the field of building materials. The preparation method of the reinforced ardealite aggregate comprises the following steps: mixing the ardealite, the cement, the primary aluminum ash, the water and the ettringite crystal form control agent to obtain a mixture; carrying out extrusion molding and autoclaved curing on the mixture to obtain phosphogypsum aggregate; the preparation method comprises the following steps: dipping ardealite aggregate in an organic silicon emulsion, and drying to obtain hydrophobic ardealite aggregate; and putting the hydrophobic ardealite aggregate into a strong alkali solution in which carbon dioxide is continuously introduced to react, and drying to obtain the ardealite composite material. The ardealite and the primary aluminum ash react to generate ettringite, and the ardealite and the carbon dioxide react in a strong alkali solution to generate calcite to synergistically improve the strength of the aggregate, so that the reinforced ardealite aggregate disclosed by the invention can be used for preparing an ultra-high performance concrete material with compressive strength higher than 150MPa; the problem of shortage of natural quartz sand resources is solved while ardealite resources and a large amount of accumulated primary aluminum ash resources are consumed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] The present invention relates to the technical field of building materials, and in particular to a reinforced phosphogypsum aggregate, an ultra-high performance concrete material and a preparation method thereof. Background Art

[0004] The compressive strength of high-performance concrete can generally reach 50-120MPa, but for some special structural applications, such as long-span bridges, key parts of high-rise buildings, marine engineering structures, etc., the strength of high-performance concrete still cannot meet the design requirements. At the same time, the tensile strength of traditional concrete is even weaker, and its tensile strength is only 1 / 10-1 / 20 of the compressive strength, which makes it easy for concrete structures to crack when subjected to bending, tension or shear loads, thereby affecting the durability and safety of the structure.

[0005] On the other hand, ordinary concrete is easily corroded by environmental factors during long-term use, such as chloride ion corrosion, carbonization, sulfate corrosion, etc. In the marine environment, chloride ions in seawater will penetrate into the interior of the concrete, causing steel corrosion, and then causing cracking, peeling and other damage to the concrete structure. For some infrastructure projects, such as port terminals, cross-sea bridges, etc., their service life is required to be as long as decades or even hundreds of years, and the durability of traditional concrete is difficult to meet such stringent requirements. Therefore, this patent proposes an ultra-high performance concrete material with high strength and high durability to solve the technical limitations of its application in existing infrastructure projects.

[0006] Phosphogypsum is an industrial waste residue from the industrial preparation of phosphoric acid. At present, the stockpile of phosphogypsum in my country has reached about 700 million tons, and is increasing at a rate of 80 million tons per year. The utilization of phosphogypsum is imminent. The present invention efficiently utilizes solid wastes such as phosphogypsum and primary aluminum ash to prepare reinforced phosphogypsum aggregate, and can provide a new idea for carbon fixation. The use of high-dosage reinforced phosphogypsum aggregate can prepare ultra-high performance concrete with a compressive strength of more than 150MPa. Summary of the invention

[0008] The technical problem to be solved by the patent of this invention is to provide a reinforced phosphogypsum aggregate, an ultra-high performance concrete material and a preparation method thereof in view of the above shortcomings.

[0009] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0010] In one aspect of the present invention, a reinforced phosphogypsum aggregate is provided. The reinforced phosphogypsum aggregate of the present invention is an artificial aggregate with a particle size of 1.18-2.36 mm obtained by extruding and autoclaving a paste prepared from phosphogypsum, cement, primary aluminum ash, water and calcium sulfoxide crystal control agent, and continuously introducing carbon dioxide into a strong alkaline solution, undergoing a series of chemical reactions, and then drying to obtain the reinforced phosphogypsum aggregate.

[0011] That is, the preparation method of the reinforced phosphogypsum aggregate comprises:

[0012] Mixing raw materials including phosphogypsum, cement, primary aluminum ash, water and ettringite crystal shape control agent to obtain a mixture;

[0013] The mixture is subjected to extrusion molding and autoclaving to obtain phosphogypsum aggregate;

[0014] The phosphogypsum aggregate is placed in an organosilicon emulsion for immersion treatment, and then dried to obtain a hydrophobic phosphogypsum aggregate;

[0015] The hydrophobic phosphogypsum aggregate is placed in a strong alkaline solution containing sodium polyphosphate, and carbon dioxide is continuously introduced into the strong alkaline solution for reaction. After the reaction is completed, the reinforced phosphogypsum aggregate is obtained after drying.

[0016] The present invention uses phosphogypsum and primary aluminum ash to react to generate ettringite, and phosphogypsum reacts with sodium hydroxide solution and carbon dioxide to generate calcium carbonate, and controls the ratio of ettringite crystal form and calcite crystal form generated during the preparation process, so that the two can better cooperate to improve the strength of the aggregate. The reinforced phosphogypsum aggregate of the present invention can replace quartz sand to prepare ultra-high performance concrete materials with a compressive strength higher than 150MPa.

[0017] Furthermore, the mass ratio of phosphogypsum: primary aluminum ash: cement: water is (60-80): (10-30): (10-20): (10-20), and the mass fraction of the main component of the ettringite crystal shape controller in the mixture is 0.5%-3%. Preferably, the ettringite crystal shape controller is a solid powder of sodium sulfate, and after mixing with water, the mass fraction of sodium sulfate in the mixture is 0.5%-3%.

[0018] Furthermore, the preparation method of the reinforced phosphogypsum aggregate comprises:

[0019] S1: drying the raw material phosphogypsum at 50-80 °C for 12-24 h, and then putting it into a ball mill to grind the raw material phosphogypsum to obtain phosphogypsum powder;

[0020] S2: Dry the raw material primary aluminum ash at 80-100°C for 12-24h;

[0021] S3: mixing phosphogypsum powder, primary aluminum ash and cement, and adding ettringite crystal shape control agent and water to obtain a mixture;

[0022] S4: Extruding the mixture by a machine, with an extrusion pressure of 10-20 MPa and an extrusion speed of 8-12 mm / min, controlling the aggregate particle size to be 1.18-2.36 mm, and then steaming the mixture at a temperature of 60-80 °C, a relative humidity greater than 90%, and 0.8-1.5 MPa for 1-3 days to obtain phosphogypsum aggregate;

[0023] S5: the phosphogypsum aggregate is placed in a 5%-20% organosilicon emulsion (the mass concentration of organosilicon in the emulsion is 5%-20%) for immersion treatment, the immersion time is 1-3 hours, the immersion temperature is 20-50°C, and the stirring speed is 50-200r / min; then, the phosphogypsum aggregate is dried at a temperature of 80-120°C for 2-5 hours to obtain a hydrophobic phosphogypsum aggregate;

[0024] S6: adding the hydrophobic treated phosphogypsum aggregate to a 1.5-3 mol / L sodium hydroxide solution, wherein the mass ratio of phosphogypsum raw material to sodium hydroxide solid is (1-2):1 (herein, sodium hydroxide solid refers to the content of sodium hydroxide solid added when the sodium hydroxide solution is prepared), adding 0.5%-2% sodium polyphosphate to the sodium hydroxide solution (that is, after the sodium polyphosphate is added to the sodium hydroxide solution, the mass concentration of the sodium polyphosphate is 0.5%-2%), so as to adjust the crystal form of calcium carbonate to be a calcite crystal form, controlling the reaction temperature at 20-60 °C, maintaining the pH at 11-13, and continuously introducing carbon dioxide at a carbon dioxide flow rate of 1L / h-2L / h, a reaction time of 1-2h, and continuously stirring the solution at a stirring rate of 50-200r / min;

[0025] S7: After the reaction is completed, the phosphogypsum aggregate is dried at 50-80°C for 24-48h to obtain reinforced phosphogypsum aggregate.

[0026] Furthermore, in the phosphogypsum, the calcium sulfate content is 70%-95%, the phosphoric acid content is 0.5-8%, the phosphate content is 1%-8%, the fluoride content is 0.1%-2%, the arsenic content is less than 30 mg / kg, the lead content is less than 100 mg / kg, the cadmium content is less than 10 mg / kg, and the mercury content is less than 5 mg / kg.

[0027] Furthermore, the primary aluminum ash has an aluminum content of 15%-70%, a fluorine content of 1%-5%, a silicon content of 2%-10%, a sodium content of 0.5-3%, a lead content of less than 0.1%, a cadmium content of less than 0.01%, and a chromium content of less than 0.1%.

[0028] The second aspect of the present invention provides an ultra-high performance concrete material prepared using the above-mentioned reinforced phosphogypsum aggregate, comprising the following raw materials in parts by weight: 600-800 parts of cement, 150-300 parts of fly ash beads, 100-300 parts of silica fume, 450-600 parts of reinforced phosphogypsum aggregate, 100-200 parts of quartz sand, 160-240 parts of hook steel fiber, 30-40 parts of water reducer, and 150-200 parts of water.

[0029] The cement is 52.5 grade ordinary Portland cement.

[0030] The fly ash is fly ash micro beads, with a loss on ignition of ≤5.5%, a water requirement ratio of ≤90%, and a spherical particle volume rate of ≥92%.

[0031] The SiO2 mass content in the silica ash is ≥95%, and the specific surface area is ≥14500m 2 / kg, 28d activity index ≥100%.

[0032] The reinforced phosphogypsum aggregate prepared by the present invention has a cylinder compressive strength of 10-15 MPa and an apparent density of 2135-2492 kg / m 3 , water absorption rate 5.2%-9.5%.

[0033] The hook steel fiber has a nominal length of 25-40 mm, a diameter of 0.25-0.60 mm, and a tensile strength greater than 1600 MPa.

[0034] The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is greater than 30%.

[0035] The present invention adopts reinforced phosphogypsum aggregate to prepare ultra-high performance concrete materials, which can solve the problem of industrial solid waste treatment, is beneficial to environmental protection, and can effectively solve the current problem of scarcity of commonly used aggregate resources for ultra-high performance concrete, the problem of large-scale accumulation of phosphogypsum and primary aluminum ash, and save resources and energy; the use of mineral admixtures such as polycarboxylic acid high-efficiency water reducer and fly ash microbeads can optimize the working performance of concrete mixtures, improve the compactness and homogeneity of concrete, and reduce the shrinkage of ultra-high performance concrete to a certain extent. The present invention combines solid waste phosphogypsum and primary aluminum ash, effectively solves the problem of bulk solid waste accumulation, and prepares ultra-high performance concrete with high compressive strength and high durability.

[0036] A third aspect of the present invention further provides a method for preparing an ultra-high performance concrete material by strengthening phosphogypsum aggregate, comprising the following steps:

[0037] S1: Mix cement, silica fume, fly ash, quartz sand and reinforced phosphogypsum aggregate for 3 minutes, then add water and water reducing agent and stir for 3 minutes, and finally add hook steel fiber and continue stirring for 3 minutes.

[0038] S2: After mold filling, vibration and molding, the surface is covered with a waterproof film for film curing, and then the mold is removed and placed in a standard curing environment for curing for 28 days to obtain the reinforced phosphogypsum aggregate ultra-high performance concrete material.

[0039] Compared with the prior art, the present invention is beneficial in that:

[0040] (1) The present invention uses phosphogypsum to react with primary aluminum ash to generate ettringite, and phosphogypsum reacts with sodium hydroxide solution and carbon dioxide to generate calcite crystals. The aggregate strength is synergistically improved by controlling the ratio of ettringite crystals to calcite crystals. At the same time, the reaction process can provide a new way to fix carbon.

[0041] (2) The present invention adopts reinforced phosphogypsum aggregate to prepare ultra-high performance concrete material, which can greatly absorb phosphogypsum resources and a large amount of accumulated primary aluminum ash resources; on the other hand, the use of reinforced phosphogypsum aggregate as aggregate solves the problem of scarce natural quartz sand resources.

[0042] (3) Compared with the traditional method of using quartz sand to prepare ultra-high performance concrete materials, the present invention uses reinforced phosphogypsum aggregate to produce ultra-high performance concrete with a compressive strength higher than 150 MPa. DETAILED DESCRIPTION

[0044] The following further illustrates the application and preparation method of the reinforced phosphogypsum aggregate of the present application in UHPC materials with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means adopted in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The following will combine the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] A reinforced phosphogypsum aggregate, wherein the preparation method of the reinforced phosphogypsum aggregate comprises:

[0046] Mixing raw materials including phosphogypsum, cement, primary aluminum ash, water and ettringite crystal shape control agent to obtain a mixture;

[0047] The mixture is subjected to extrusion molding and autoclaving to obtain phosphogypsum aggregate;

[0048] The phosphogypsum aggregate is placed in an organosilicon emulsion for immersion treatment, and then dried to obtain a hydrophobic phosphogypsum aggregate;

[0049] The hydrophobic phosphogypsum aggregate is placed in a strong alkaline solution containing sodium polyphosphate, and carbon dioxide is continuously introduced into the strong alkaline solution for reaction. After the reaction is completed, the reinforced phosphogypsum aggregate is obtained after drying.

[0050] In some examples, the phosphogypsum: primary aluminum ash: cement: water = (60-80): (10-30): (10-20): (10-20) (mass ratio), and the mass fraction of the main component of the ettringite crystal shape controller in the mixture is 0.5%-3%. Preferably, the ettringite crystal shape controller is a solid powder of sodium sulfate, and after mixing with water, the mass fraction of sodium sulfate in the mixture is 0.5%-3%.

[0051] In a specific example of the present invention, the method for preparing the reinforced phosphogypsum aggregate comprises:

[0052] S1: drying the raw material phosphogypsum at 50-80 °C for 12-24 h, and then putting it into a ball mill to grind the raw material phosphogypsum to obtain phosphogypsum powder;

[0053] S2: Dry the raw material primary aluminum ash at 80-100°C for 12-24h;

[0054] S3: mixing phosphogypsum powder, primary aluminum ash and cement, and adding ettringite crystal shape control agent and water to obtain a mixture;

[0055] S4: Extruding the mixture by a machine, with an extrusion pressure of 10-20 MPa and an extrusion speed of 8-12 mm / min, controlling the aggregate particle size to be 1.18-2.36 mm, and then steaming the mixture at a temperature of 60-80 °C, a relative humidity greater than 90%, and 0.8-1.5 MPa for 1-3 days to obtain phosphogypsum aggregate;

[0056] S5: the phosphogypsum aggregate is immersed in 5%-20% organosilicon emulsion for 1-3 hours, the immersion temperature is 20-50°C, and the stirring speed is 50-200r / min; then, the phosphogypsum aggregate is dried at 80-120°C for 2-5 hours to obtain hydrophobic phosphogypsum aggregate;

[0057] S6: adding the hydrophobic treated phosphogypsum aggregate to a 1.5-3 mol / L sodium hydroxide solution, wherein the mass ratio of phosphogypsum raw material to sodium hydroxide solid is (1-2):1, and adding 0.5%-2% sodium polyphosphate to the sodium hydroxide solution (that is, after sodium polyphosphate is added to the sodium hydroxide solution, the mass concentration of sodium polyphosphate is 0.5%-2%) to adjust the crystal form of calcium carbonate to be a calcite crystal form, controlling the reaction temperature at 20-60 °C, maintaining pH=11-13, and continuously introducing carbon dioxide at a carbon dioxide flow rate of 1L / h-2L / h, a reaction time of 1-2h, and continuously stirring the solution at a stirring rate of 50-200r / min;

[0058] S7: After the reaction is completed, the phosphogypsum aggregate is dried at 50-80°C for 24-48h to obtain reinforced phosphogypsum aggregate.

[0059] In the following specific embodiments,

[0060] The phosphogypsum has a calcium sulfate content of 70%-95%, a phosphoric acid content of 0.5-8%, a phosphate content of 1%-8%, a fluoride content of 0.1%-2%, an arsenic content of less than 30 mg / kg, a lead content of less than 100 mg / kg, a cadmium content of less than 10 mg / kg, and a mercury content of less than 5 mg / kg;

[0061] The primary aluminum ash has an aluminum content of 15%-70%, a fluorine content of 1%-5%, a silicon content of 2%-10%, a sodium content of 0.5-3%, a lead content of less than 0.1%, a cadmium content of less than 0.01%, and a chromium content of less than 0.1%.

[0062] The cement is 52.5 grade ordinary Portland cement.

[0063] The fly ash is fly ash micro beads, with a loss on ignition of ≤5.5%, a water requirement ratio of ≤90%, and a spherical particle volume rate of ≥92%.

[0064] The SiO2 mass content in the silica ash is ≥95%, and the specific surface area is ≥14500m 2 / kg, 28d activity index ≥100%.

[0065] The reinforced phosphogypsum aggregate obtained by the present invention has a cylinder compressive strength of 10-15 MPa and an apparent density of 2135-2492 kg / m 3 , water absorption rate 5.2%-9.5%.

[0066] The hook steel fiber has a nominal length of 25-40 mm, a diameter of 0.25-0.60 mm, and a tensile strength greater than 1600 MPa.

[0067] The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is greater than 30%.

[0068] The water is ordinary tap water, which meets the requirements of "Standard for Water Use in Concrete" JGJ63.

[0069] The organosilicon emulsion is a commercially available composite ionic hydroxyl silicone oil emulsion with a silicone mass concentration of 10%.

[0070] Example 1

[0071] A method for preparing UHPC material from reinforced phosphogypsum aggregate comprises the following raw materials in parts by weight:

[0072] 780 parts of cement, 200 parts of fly ash beads, 150 parts of silica fume, 450 parts of reinforced phosphogypsum aggregate, 200 parts of quartz sand, 240 parts of hook steel fiber, 35 parts of water reducer, and 150 parts of water.

[0073] The preparation method of reinforced phosphogypsum aggregate comprises the following steps:

[0074] S1: drying the raw material phosphogypsum at 50 °C for 24 h and then putting it into a ball mill to grind the raw material phosphogypsum to obtain phosphogypsum powder;

[0075] S2: Dry the raw material primary aluminum ash at 90 °C for 12 h;

[0076] S3: After mixing phosphogypsum powder, primary aluminum ash and cement, add ettringite crystal shape controller and water and stir to obtain a mixture. The ettringite crystal shape controller is solid sodium sulfate powder. After mixing with water, the mass fraction of sodium sulfate is 3%. Phosphogypsum: primary aluminum ash: cement: water = 60: 30: 10: 20 (mass ratio).

[0077] S4: The mixture is extruded by a machine at an extrusion pressure of 10 MPa and an extrusion speed of 8 mm / min, and the aggregate particle size is controlled to be 1.18-2.36 mm. It is then steamed at a temperature of 80°C, a relative humidity greater than 90%, and 1.5 MPa for 1 day to obtain phosphogypsum aggregate.

[0078] S5: The phosphogypsum aggregate is immersed in 5% organosilicon emulsion for 3 hours at a temperature of 50°C and a stirring speed of 50 r / min. Subsequently, the phosphogypsum aggregate is dried at 80°C for 2 hours to obtain hydrophobic phosphogypsum aggregate.

[0079] S6: Add the above hydrophobic treated phosphogypsum aggregate into 1.5 mol / L sodium hydroxide solution, the mass ratio of phosphogypsum raw material: sodium hydroxide solid is 1:1, add 0.5% sodium polyphosphate into the sodium hydroxide solution to adjust the crystal form of calcium carbonate to calcite, control the reaction temperature at 20°C, maintain pH=13, and continuously introduce carbon dioxide, the carbon dioxide flow rate is 2L / h, the reaction time is 2h, and the solution is continuously stirred at a stirring rate of 50r / min.

[0080] S7: After the reaction is completed, the phosphogypsum aggregate is dried at 50° C. for 48 hours to obtain reinforced phosphogypsum aggregate.

[0081] The method for preparing the ultra-high performance concrete material of this embodiment comprises the following steps:

[0082] S1: Mix cement, silica fume, fly ash, quartz sand and reinforced phosphogypsum aggregate for 3 minutes, then add water and water reducing agent and stir for 3 minutes, and finally add hook steel fiber and continue stirring for 3 minutes.

[0083] S2: After mold filling, vibration and molding, the surface is covered with a waterproof film for film curing, and then the mold is removed and placed in a standard curing environment for curing for 28 days to obtain the reinforced phosphogypsum aggregate ultra-high performance concrete material.

[0084] Example 2

[0085] A method for preparing UHPC material from reinforced phosphogypsum aggregate comprises the following raw materials in parts by weight:

[0086] 600 parts of cement, 230 parts of fly ash beads, 300 parts of silica fume, 600 parts of reinforced phosphogypsum aggregate, 100 parts of quartz sand, 210 parts of hook steel fiber, 35 parts of water reducer, and 170 parts of water.

[0087] The preparation method of reinforced phosphogypsum aggregate comprises the following steps:

[0088] S1: drying the raw material phosphogypsum at 60 °C for 20 h and then putting it into a ball mill to grind the raw material phosphogypsum to obtain phosphogypsum powder;

[0089] S2: Dry the raw material primary aluminum ash at 80 °C for 24 h;

[0090] S3: After mixing phosphogypsum powder, primary aluminum ash and cement, add ettringite crystal shape controller and water to stir to obtain a mixture. The ettringite crystal shape controller is solid sodium sulfate powder. After mixing with water, the mass fraction of sodium sulfate is 2%. Phosphogypsum: primary aluminum ash: cement: water = 70:25:15:15 (mass ratio).

[0091] S4: The mixture is extruded by a machine at an extrusion pressure of 13 MPa and an extrusion speed of 9 mm / min, and the aggregate particle size is controlled to be 1.18-2.36 mm. The mixture is then steamed at a temperature of 60°C, a relative humidity greater than 90%, and 1.2 MPa for 2 days to obtain phosphogypsum aggregate.

[0092] S5: The phosphogypsum aggregate is immersed in 10% organosilicon emulsion for 2 hours at a temperature of 40°C and a stirring speed of 100 r / min. Subsequently, the phosphogypsum aggregate is dried at 90°C for 3 hours to obtain hydrophobic phosphogypsum aggregate.

[0093] S6: Add the above hydrophobic treated phosphogypsum aggregate into 2 mol / L sodium hydroxide solution, the mass ratio of phosphogypsum raw material: sodium hydroxide solid is 1.4:1, 1% sodium polyphosphate is added to the sodium hydroxide solution to adjust the crystal form of calcium carbonate to calcite, the reaction temperature is controlled at 35 °C, pH=11 is maintained, and carbon dioxide is continuously introduced, the carbon dioxide flow rate is 1.4L / h, the reaction time is 2h, and the solution is continuously stirred at a stirring rate of 100r / min.

[0094] S7: After the reaction is completed, the phosphogypsum aggregate is dried at 60° C. for 36 hours to obtain reinforced phosphogypsum aggregate.

[0095] The method for preparing the ultra-high performance concrete material of this embodiment comprises the following steps:

[0096] S1: Mix cement, silica fume, fly ash, quartz sand and reinforced phosphogypsum aggregate for 3 minutes, then add water and water reducing agent and stir for 3 minutes, and finally add hook steel fiber and continue stirring for 3 minutes.

[0097] S2: After mold filling, vibration and molding, the surface is covered with a waterproof film for film curing, and then the mold is removed and placed in a standard curing environment for curing for 28 days to obtain the reinforced phosphogypsum aggregate ultra-high performance concrete material.

[0098] Example 3

[0099] A method for preparing UHPC material from reinforced phosphogypsum aggregate comprises the following raw materials in parts by weight:

[0100] 700 parts of cement, 300 parts of fly ash beads, 130 parts of silica fume, 500 parts of reinforced phosphogypsum aggregate, 150 parts of quartz sand, 180 parts of hook steel fiber, 40 parts of water reducer, and 180 parts of water.

[0101] The preparation method of reinforced phosphogypsum aggregate comprises the following steps:

[0102] S1: drying the raw material phosphogypsum at 70 °C for 16 h and then putting it into a ball mill to grind the raw material phosphogypsum to obtain phosphogypsum powder;

[0103] S2: Dry the raw material primary aluminum ash at 100 °C for 12 h;

[0104] S3: After mixing phosphogypsum powder, primary aluminum ash and cement, add ettringite crystal shape controller and water to stir to obtain a mixture. The ettringite crystal shape controller is solid sodium sulfate powder. After mixing with water, the mass fraction of sodium sulfate is 1%. Phosphogypsum: primary aluminum ash: cement: water = 75:20:15:15 (mass ratio).

[0105] S4: The mixture is extruded by a machine at an extrusion pressure of 16 MPa and an extrusion speed of 10 mm / min, and the aggregate particle size is controlled to be 1.18-2.36 mm. The mixture is then steamed at a temperature of 70°C, a relative humidity greater than 90%, and 1.0 MPa for 1 day to obtain phosphogypsum aggregate.

[0106] S5: The phosphogypsum aggregate is immersed in 15% organosilicon emulsion for 1.5 hours, at a temperature of 30°C and a stirring speed of 150r / min. Subsequently, the phosphogypsum aggregate is dried at 100°C for 4 hours to obtain hydrophobic phosphogypsum aggregate.

[0107] S6: Add the above hydrophobic treated phosphogypsum aggregate to 2.5 mol / L sodium hydroxide solution, the mass ratio of phosphogypsum raw material: sodium hydroxide solid is 1.8:1, 1.5% sodium polyphosphate is added to the sodium hydroxide solution to adjust the crystal form of calcium carbonate to calcite, the reaction temperature is controlled at 50 °C, the pH is maintained at 12, and carbon dioxide is continuously introduced, the carbon dioxide flow rate is 1.8 L / h, the reaction time is 1.5 h, and the solution is continuously stirred at a stirring rate of 150 r / min.

[0108] S7: After the reaction is completed, the phosphogypsum aggregate is dried at 70° C. for 30 hours to obtain reinforced phosphogypsum aggregate.

[0109] The method for preparing the ultra-high performance concrete material of this embodiment comprises the following steps:

[0110] S1: Mix cement, silica fume, fly ash, quartz sand and reinforced phosphogypsum aggregate for 3 minutes, then add water and water reducing agent and stir for 3 minutes, and finally add hook steel fiber and continue stirring for 3 minutes.

[0111] S2: After mold filling, vibration and molding, the surface is covered with a waterproof film for film curing, and then the mold is removed and placed in a standard curing environment for curing for 28 days to obtain the reinforced phosphogypsum aggregate ultra-high performance concrete material.

[0112] Example 4

[0113] A method for preparing UHPC material from reinforced phosphogypsum aggregate comprises the following raw materials in parts by weight:

[0114] 800 parts of cement, 150 parts of fly ash beads, 180 parts of silica fume, 600 parts of reinforced phosphogypsum aggregate, 100 parts of quartz sand, 160 parts of hook steel fiber, 30 parts of water reducer, and 200 parts of water.

[0115] The preparation method of reinforced phosphogypsum aggregate comprises the following steps:

[0116] S1: drying the raw material phosphogypsum at 80°C for 12 hours and then putting it into a ball mill to grind the raw material phosphogypsum to obtain phosphogypsum powder;

[0117] S2: Dry the raw material primary aluminum ash at 85 °C for 24h;

[0118] S3: After mixing phosphogypsum powder, primary aluminum ash and cement, add ettringite crystal shape controller and water to stir to obtain a mixture, wherein the ettringite crystal shape controller is solid sodium sulfate powder. After mixing with water, the mass fraction of sodium sulfate is 0.5%; phosphogypsum: primary aluminum ash: cement: water = 80:10:20:10 (mass ratio);

[0119] S4: Extruding the mixture by a machine, with an extrusion pressure of 20 MPa and an extrusion speed of 12 mm / min, controlling the aggregate particle size to be 1.18-2.36 mm, and then steaming at a temperature of 80 ° C, a relative humidity greater than 90%, and 0.8 MPa for 3 days to obtain phosphogypsum aggregate;

[0120] S5: The phosphogypsum aggregate is immersed in 20% organosilicon emulsion for 1 hour, the immersion temperature is 20°C, and the stirring speed is 200r / min. Subsequently, the phosphogypsum aggregate is dried at 120°C for 2 hours to obtain hydrophobic phosphogypsum aggregate;

[0121] S6: adding the hydrophobic treated phosphogypsum aggregate to a 3 mol / L sodium hydroxide solution, the mass ratio of phosphogypsum raw material to sodium hydroxide solid is 2:1, adding 2% sodium polyphosphate to the sodium hydroxide solution to adjust the crystal form of calcium carbonate to calcite, controlling the reaction temperature at 60 °C, maintaining pH=11, and continuously introducing carbon dioxide at a flow rate of 1 L / h, a reaction time of 2 h, and continuously stirring the solution at a stirring rate of 200 r / min;

[0122] S7: After the reaction is completed, the phosphogypsum aggregate is dried at 80° C. for 24 hours to obtain reinforced phosphogypsum aggregate.

[0123] The phosphogypsum has a calcium sulfate content of 70%-95%, a phosphoric acid content of 0.5-8%, a phosphate content of 1%-8%, a fluoride content of 0.1%-2%, an arsenic content of less than 30 mg / kg, a lead content of less than 100 mg / kg, a cadmium content of less than 10 mg / kg, and a mercury content of less than 5 mg / kg.

[0124] The method for preparing the ultra-high performance concrete material of this embodiment comprises the following steps:

[0125] S1: Mix cement, silica fume, fly ash, quartz sand and reinforced phosphogypsum aggregate for 3 minutes, then add water and water reducing agent and stir for 3 minutes, and finally add hook steel fiber and continue stirring for 3 minutes;

[0126] S2: After mold filling, vibration and molding, the surface is covered with a waterproof film for film curing, and then the mold is removed and placed in a standard curing environment for curing for 28 days to obtain the reinforced phosphogypsum aggregate ultra-high performance concrete material.

[0127] Comparative Example 1

[0128] This comparative example is basically the same as Example 1, except that the reinforced phosphogypsum aggregate is replaced by 1.18-2.36 mm machine-made sand.

[0129] Comparative Example 2

[0130] This comparative example is basically the same as Example 1, except that the reinforced phosphogypsum aggregate is replaced by 1.18-2.36 mm quartz sand.

[0131] Comparative Example 3

[0132] This comparative example is basically the same as Example 1, except that sodium sulfate and sodium polyphosphate are not added during the preparation of the reinforced phosphogypsum aggregate.

[0133] Comparative Example 4

[0134] This comparative example is substantially the same as Example 1, except that sodium polyphosphate is not added during the preparation of the reinforced phosphogypsum aggregate.

[0135] Comparative Example 5

[0136] This comparative example is basically the same as Example 1, except that no sodium sulfate is added during the preparation of the reinforced phosphogypsum aggregate.

[0137] Comparative Example 6

[0138] This comparative example is basically the same as Example 1, except that in the preparation process of reinforced phosphogypsum aggregate, the mass fraction of sodium sulfate is 8%.

[0139] Comparative Example 7

[0140] This comparative example is basically the same as Example 1, except that 5% of sodium polyphosphate is added during the preparation of the reinforced phosphogypsum aggregate.

[0141] Table 1 - Performance of ultra-high performance concrete materials prepared in Examples 1-4 and Comparative Examples 1-7

[0142]

[0143] As can be seen from Table 1, compared with Comparative Examples 1-7, the reinforced phosphogypsum aggregate ultra-high performance concrete material obtained in the embodiment of the present invention has high strength, and its compressive strength is equivalent to that of traditional high-ductility cement-based materials, and its tensile strength is doubled compared with traditional high-ductility cement-based materials. It can be applied to various large-scale projects, which not only improves the strength of the concrete itself, but also provides a new idea for the solidification of phosphogypsum, primary aluminum ash and carbon dioxide, and has important economic and environmental benefits. The performance of the concrete materials of Comparative Examples 3-7 is much worse than that of Example 1 of the present invention. This is mainly due to the different ratios of ettringite crystals and calcite crystals in the reinforced phosphogypsum aggregate. When the sodium sulfate dosage is too high, the ettringite crystals in the cement stone structure will grow too fast and disorderly. Too many ettringite crystals are generated in a large amount in a short period of time, forming a thick coating layer on the surface of cement particles, hindering the normal hydration reaction of cement; when there is an excessive amount of sodium polyphosphate, the calcium carbonate crystals cannot grow normally into the expected calcite crystals, but form some irregular tiny particle agglomerates; these reasons make it impossible for the ettringite crystals and calcite crystals in the reinforced phosphogypsum aggregate to play a better synergistic effect, thereby resulting in a decrease in the performance of the concrete material.

[0144] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A reinforced phosphogypsum aggregate, characterized in that: The preparation method of the reinforced phosphogypsum aggregate comprises the steps of: Mixing raw materials including phosphogypsum, cement, primary aluminum ash, water and ettringite crystal shape control agent to obtain a mixture; The mixture is subjected to extrusion molding and autoclaving to obtain phosphogypsum aggregate; The phosphogypsum aggregate is placed in an organosilicon emulsion for impregnation treatment, and then dried to obtain a hydrophobic phosphogypsum aggregate; The hydrophobic phosphogypsum aggregate is placed in a strong alkaline solution containing sodium polyphosphate, and carbon dioxide is continuously introduced into the strong alkaline solution for reaction. After the reaction is completed, the reinforced phosphogypsum aggregate is obtained after drying.

2. A reinforced phosphogypsum aggregate according to claim 1, characterized in that: The mass ratio of the phosphogypsum: primary aluminum ash: cement: water is (60-80):(10-30):(10-20):(10-20), and the mass fraction of the main component of the calcium sulfide crystal shape controller in the mixture is 0.5%-3%.

3. A reinforced phosphogypsum aggregate according to claim 1, characterized in that: The ettringite crystal shape controller is sodium sulfate solid powder.

4. A reinforced phosphogypsum aggregate according to claim 1, characterized in that: The preparation method of the reinforced phosphogypsum aggregate comprises: S1: drying the raw material phosphogypsum at 50-80 °C for 12-24 h, and then putting it into a ball mill to grind the raw material phosphogypsum to obtain phosphogypsum powder; S2: Dry the raw material primary aluminum ash at 80-100°C for 12-24h; S3: mixing phosphogypsum powder, primary aluminum ash and cement, and adding ettringite crystal shape control agent and water to obtain a mixture; S4: Extruding the mixture by a machine, with an extrusion pressure of 10-20 MPa and an extrusion speed of 8-12 mm / min, controlling the aggregate particle size to be 1.18-2.36 mm, and then steaming the mixture at a temperature of 60-80 °C, a relative humidity greater than 90%, and 0.8-1.5 MPa for 1-3 days to obtain phosphogypsum aggregate; S5: The phosphogypsum aggregate is immersed in 5%-20% organosilicon emulsion for 1-3 hours, the immersion temperature is 20-50°C, and the stirring speed is 50-200r / min; then, the phosphogypsum aggregate is dried at 80-120°C for 2-5 hours to obtain hydrophobic phosphogypsum aggregate; S6: adding the hydrophobic phosphogypsum aggregate to a 1.5-3 mol / L sodium hydroxide solution, wherein the mass ratio of the phosphogypsum raw material to the sodium hydroxide solid is (1-2):1, adding 0.5%-2% sodium polyphosphate to the sodium hydroxide solution to adjust the crystal form of calcium carbonate to be a calcite crystal form, controlling the reaction temperature at 20-60 °C, maintaining the pH at 11-13, and continuously introducing carbon dioxide at a flow rate of 1 L / h-2 L / h, a reaction time of 1-2 h, and continuously stirring the solution at a stirring rate of 50-200 r / min; S7: After the reaction is completed, the phosphogypsum aggregate is dried at 50-80°C for 24-48h to obtain reinforced phosphogypsum aggregate.

5. A reinforced phosphogypsum aggregate according to claim 1, characterized in that: The phosphogypsum has a calcium sulfate content of 70%-95%, a phosphoric acid content of 0.5-8%, a phosphate content of 1%-8%, a fluoride content of 0.1%-2%, an arsenic content of less than 30 mg / kg, a lead content of less than 100 mg / kg, a cadmium content of less than 10 mg / kg, and a mercury content of less than 5 mg / kg.

6. A reinforced phosphogypsum aggregate according to claim 1, characterized in that: The primary aluminum ash has an aluminum content of 15%-70%, a fluorine content of 1%-5%, a silicon content of 2%-10%, a sodium content of 0.5-3%, a lead content of less than 0.1%, a cadmium content of less than 0.01%, and a chromium content of less than 0.1%.

7. An ultra-high performance concrete material prepared using the reinforced phosphogypsum aggregate according to claims 1-6, characterized in that: The invention comprises the following raw materials in parts by weight: 600-800 parts of cement, 150-300 parts of fly ash microbeads, 100-300 parts of silica fume, 450-600 parts of reinforced phosphogypsum aggregate, 100-200 parts of quartz sand, 160-240 parts of hook steel fiber, 30-40 parts of water reducer and 150-200 parts of water.

8. The ultra-high performance concrete material according to claim 7, characterized in that: The reinforced phosphogypsum aggregate has a cylinder compressive strength of 10-15 MPa and an apparent density of 2135-2492 kg / m 3 , water absorption rate 5.2%-9.5%.

9. The ultra-high performance concrete material according to claim 7, characterized in that: The particle size of the phosphogypsum aggregate is 1.18-2.36 mm.

10. A method for preparing the ultra-high performance concrete material according to claim 7, characterized in that: The method comprises the following steps: mixing cement, silica fume, fly ash, quartz sand and reinforced phosphogypsum aggregate, adding water and water reducing agent and stirring, adding hook steel fiber and continuing to stir and mix; After the mixed material is molded, vibrated and formed, the surface is covered with a waterproof film for film curing, the mold is removed, and the material is placed in a standard curing environment for curing to obtain reinforced phosphogypsum aggregate ultra-high performance concrete material.

Citation Information

Patent Citations

  • Phosphogypsum micro-expansion lightweight aggregate ultra-high performance concrete and preparation method thereof

    CN118307270A

  • Recycled aggregate strengthening method based on carbonized product crystal form control and application

    CN118834033A

  • Sprayed concrete composition for inorganic self-healing cross section repair and cross section repair method for concrete structures using the same

    KR102668195B1

  • Phosphogypsum non-sintered ceramsite light aggregate and preparation method thereof

    US20210163353A1

  • Single-step low-temperature calcium carbonate production through carbon dioxide sequestration of mineral materials to make concrete

    US20230257276A1